2017
DOI: 10.1016/j.celrep.2017.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia Impairs Neutrophil Mobilization Leading to Enhanced Metastatic Seeding

Abstract: Preexisting diabetes is a risk factor for the development of multiple types of cancer. Additionally, diabetic patients face a poorer prognosis when diagnosed with cancer. To gain insight into the effects of hyperglycemia, a hallmark of diabetes, on tumor growth and metastatic progression, we combined mouse models of cancer and hyperglycemia. We show that while hyperglycemia attenuates primary tumor growth, it concomitantly increases metastatic seeding in a distant organ. We further show that the increase in me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 26 publications
2
29
0
1
Order By: Relevance
“…The expression of CXCR1/2 decreased after bariatric surgery in female adipose tissue [29]. Moreover, CXCR2deficient mice are resistant to diet-induced insulin resistance and diabetes, mainly because CXCL5 blocks insulin signaling in muscle by activating the muscle Jak/STAT/SOCS pathway through the CXCR2 receptor [30]. In accordance with this finding, our RNA-seq analysis revealed that the CXCR1 and CXCR2 genes were significantly upregulated in patients with type 2 diabetes compared with healthy controls.…”
Section: Discussionsupporting
confidence: 82%
“…The expression of CXCR1/2 decreased after bariatric surgery in female adipose tissue [29]. Moreover, CXCR2deficient mice are resistant to diet-induced insulin resistance and diabetes, mainly because CXCL5 blocks insulin signaling in muscle by activating the muscle Jak/STAT/SOCS pathway through the CXCR2 receptor [30]. In accordance with this finding, our RNA-seq analysis revealed that the CXCR1 and CXCR2 genes were significantly upregulated in patients with type 2 diabetes compared with healthy controls.…”
Section: Discussionsupporting
confidence: 82%
“…Thirdly, immune cell activation and dysfunction have been described in COPD, atherosclerosis and T2D, and linked with adverse disease outcomes (figure 1c). Clearly, neutrophils are not the only cell that show altered functionality in these three diseases, but the fact that neutrophil dysfunction occurs in COPD, atherosclerosis and T2D may provide novel links between these diseases [22,42,43]. This cellular dysfunction may represent a physiological response to a pathological event, but there is increasing evidence that chronic inflammation (as seen in COPD, atherosclerosis and T2D) can contribute to a shift in immune cell phenotype or subpopulation, changing the cell's usual response to an inflammatory insult, and increasing the potential for damage ( figure 1c).…”
Section: An Overview Of Mechanisms For Multimorbiditymentioning
confidence: 99%
“…While neutrophils are not the only cells that play a role in COPD, atherosclerosis and T2D, they are the most abundant immune cells found in lung secretions of patients diagnosed with COPD and their products have been shown to cause all facets of lung disease in animal and cell models (from chronic bronchitis to emphysema); correlating with disease severity and decline [19,20]. Recent advances in imaging technologies have also identified that neutrophils are present in the lipid core of human plaques and neutrophilia correlates with the number of rupture-prone lesions [21] and, although less studied, diabetic patients, rats and mice clearly demonstrate consistent defects of neutrophil chemotactic, phagocytic and microbicidal activities [22]. Together, this suggests neutrophils may provide a link between these three disease areas.…”
Section: Introductionmentioning
confidence: 99%
“…At the inflammation site, neutrophils display a variety of functional responses ranging from phagocytosis and respiratory burst to the extracellular release of their granule contents, which includes proteases and other microbicidal molecules as well as granule protein embedded DNA traps (NETosis) . However, growing evidence suggests a crucial regulatory role for neutrophils in tumor establishment and progression . Recent studies also document the morphological and functional heterogeneity among TANs and their association with protumor or antitumor responses depending on the TME they are part of .…”
Section: Introductionmentioning
confidence: 99%